The Effects of Spiritual Leadership and Transformational Leadership on Happiness at Work in the Digital 4.0 Era - Sudianto, Sudianto; Nugraha, Andika Prasetya; Mulyadi, Mulyadi; Fadlililah, Andi Hidayatul (University of Merdeka Malang, 2024)
Appropriate leadership will greatly affect happiness at Work, which will later affect the expected performance. This study used quantitative methods and measuring instruments using questionnaires distributed to respondents. The population in this study totaled 108 civil servants at the Regional Secretariat of the Karimun Regency Government. Meanwhile, in determining the number of samples in this study, the Slovin method was used to obtain a sample size of 85 employees who were used as respondents. The analysis test tool in this study was Smart-PLS software version 3.0 and IBM SPSS software version 26.0. They were supported using VOSviewer software to map the variables considered in this study. The results of this study indicate that Spiritual Leadership obtained insignificant negative results for Happiness at Work, while Transformational Leadership obtained significant positive results for Happiness at Work. As for Relevant Predictive, a value of 0.520 is obtained where this value is above zero, meaning that the observation value is good. As for the Fit Model, an NFI value of 0.669 was obtained, where this value was above zero, meaning that the model in this study was good.